(untitled) (Altre Modernità, 2021)
The article points out the status and peculiarities of German in Romania and explores the question whether there can be borders in the communication between the speakers of the varieties of German from Germany and Romanian German. The differences in the lexical are and phraseology, as well as in the case of code-mixing and code-switching, prove that communication can succeed, as the extra-linguistic situation plays an important role in communication, as well as the openness of all communication participants.